Prioritizing research efforts to increase onfarm income generation: the case of cassavabased farmers in periurban Southern Cameroon - Duindam, J.W.; Hauser, S. (Springer, 2011)
The extent to which agricultural technologies have had an impact in the humid forest zone remains questionable as adoption levels have been low. The technologies developed emphasized on maintaining soil fertility and crop yields in short fallow systems. This chapter defines the problems and opportunities of commercialization of cassava (Manihot esculenta) production in the forest margins of peri-urban Cameroon. Cassava is the chief subsistence staple and mainly produced extensively in traditional mixed food crop fields in a short fallow rotation. The fallow period is mostly around 2-4 years with natural regrowth typically dominated by Chromolaena odorata (Ngobo et aI., 2004). The urban demand for cassava products is currently higher than the supply which improves cassava income generation potential and justifies the development of more commercially orientated fields. Yet intensification levels are low and yields are generally far below the potential attainable. Observed production increments have been mainly based on increased cassava growing area. Data from farmer interviews and group discussions in three villages in peri-urban Yaounde indicate that technologies for sustainable intensification of cassava production should target both pre- and post-harvest activities. They should focus on reduced labour requirements and pest and disease management. The technology proposed therefore re-emphasizes on returns to labour as a parameter of success and includes the involvement of farmers in technology testing. A commercial cassava field with a rotational Pueraria fallow system is discussed as a basic design. To ensure appropriateness and subsequently a higher adoption potential and hence higher impact, the system has built-in flexibility for further on-farm adaptations.